2018
DOI: 10.1002/lary.27429
|View full text |Cite
|
Sign up to set email alerts
|

Histone Variants as Stem Cell Biomarkers for Long‐Term Injection Medialization Laryngoplasty

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Z that are associated with open chromatin states and ADSC proliferation were overrepresented in the MACD + ADSC group relative to structural histones. 13 In the present study, ADSCs co-injected with MX-JC did not boost medialization volumes relative to MX-JC alone. ADSCs, with well-described immunosuppressive effects, appeared to dampen the T cell-mediated immune response to MX-JC, characterized by dendritic cells and macrophage infiltration, which may explain this observation (Table I and Figure 6).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Z that are associated with open chromatin states and ADSC proliferation were overrepresented in the MACD + ADSC group relative to structural histones. 13 In the present study, ADSCs co-injected with MX-JC did not boost medialization volumes relative to MX-JC alone. ADSCs, with well-described immunosuppressive effects, appeared to dampen the T cell-mediated immune response to MX-JC, characterized by dendritic cells and macrophage infiltration, which may explain this observation (Table I and Figure 6).…”
Section: Discussioncontrasting
confidence: 49%
“…Fixed tissues were embedded in paraffin and 5 μm sections were cut and stained with hematoxylin and eosin as previously described. 9,13 Briefly, slides were deparaffinized and stained in Harris hematoxylin solution for10 minutes then rinsed 5 minutes in running tap water. After 1-5 sec.…”
Section: Histologymentioning
confidence: 99%
“… 24 , 25 , 26 , 27 , 28 , 29 However, in a literature search on laryngeal proteomics following IL, the only entries were two previous studies from our group. 16 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…The detailed protocol for nLC‐MS/MS analysis was previously reported. 16 Briefly, solubilization of collected tissue was performed in 2% sodium dodecyl sulfate (SDS)/50 mM Tris (pH 8.2), followed by reduction with 10 mM Tris‐(carboxyethyl) phosphine hydrochloride and cysteine alkylation with 10‐mM iodoacetemide. After SDS removal samples were digested with 1:50 trypsin solution and peptides were separated by nano‐liquid chromatography (nLC) using a Q‐Exactive mass spectrometer coupled to a Dionex 3000 Rapid Separation Liquid Chromatography nano liquid chromatograph (Thermo Fisher Scientific, Bremen, Germany), with a mixture of solvents containing water, formic acid, acetonitrile, and iso‐propanol at a rate of 400 nl/min using PicoFrit/Agilent Poroshell‐packed columns.…”
Section: Methodsmentioning
confidence: 99%
“…This kind of specific marker for MSCs would be helpful for accurate evaluation of MSCs implantation approach for VF scars in the future [137]. Although, not for VF scar treatment, Voss et al recently demonstrated that histone variants are useful as ASCs biomarkers for long-term injection medialization laryngoplasty [138]. These markers would be helpful for the accurate identification of the stem cell differentiation process in the stem cell implantation approach for VF scar.…”
Section: Current Obstacles To Restoring Slp Pliabilitymentioning
confidence: 99%